Effect of self-paced sprint interval training and low-volume HIIT on cardiorespiratory fitness: the role of heart rate and power output - Hesketh, Katie L.; Shepherd, Sam O.; Wagenmakers, Anton J. M.; Cocks, Matthew; Strauss, Juliette A. (Frontiers in Physiology, 2025)
AimThe primary aim was to assess the efficacy of self-paced sprint interval training (SIT) with low-volume high-intensity interval training (LV-HIIT) when performed without encouragement on improving cardiorespiratory fitness (CRF). A secondary aim was to explore whether the effort exerted during protocols [power output (PO) and heart rate (HR)] influenced the change in CRF.MethodsIn a randomised cross-over design, 82 previously inactive adults (m/f: 26/56, 28 ± 10 years, BMI 25 ± 3 kg m−2) undertook 6-weeks of self-paced SIT (4–8 × 30 s with 120 s recovery) or LV-HIIT (6–10 × 1 min with 1 min recovery) separated by a 4-week washout period. Sessions were completed 3×/week using WattBikes, and a target of >80% HRmax was suggested during the intervals. Markers of cardio-metabolic health were assessed before and after each intervention.ResultsTraining increased VO2peak (SIT +3.1 ± 0.4 mL kg−1 min−1, LV-HIIT +2.7 ± 1.2 mL kg−1 min−1, P < 0.001) and decreased body fat % (P = 0.002), aortic pulse wave velocity (P = 0.002) and glucose tolerance 120 min following an oral glucose tolerance test (P = 0.024), with no difference between protocols (P > 0.05). When grouping participants into tertiles based on HR and PO responses (n = 27), those achieving a low HR had similar changes in VO2peak compared to the high HR group in both interventions (P > 0.05). For LV-HIIT, participants in the highest tertile for peak PO had a greater change in VO2peak compared to all other participants (Low 1.8 ± 4.1 mL kg−1 min−1, Medium 1.9 ± 3.3 mL kg−1 min−1, High 4.3 ± 3.6 ml kg−1 min−1, P = 0.020).DiscussionSix-weeks of self-paced SIT and LV-HIIT induce comparable improvements in CRF, body composition, arterial stiffness and glucose tolerance. Importantly, higher HR did not elicit superior changes in CRF, but PO achieved during LV-HIIT may influence improvements.